The Relationship Between Consultation Length and Patient Satisfaction: A Systematic Review - Fitri Surbakti, E; Sari, K (KnE Life Sciences, 2018)
The doctor–patient communication is an important clinical function in building the doctor–patient relationship that becomes the heart and art of the medicine. There are many doctors who have no effective doctor–patient communication and no longer have consultation time that creates complaints and dissatisfaction for the patient. Patient satisfaction is strongly influenced by the quality of communication between him and the doctor. This is a systematic review showing PRISMA flowchart using online databases such as ProQuest and Google Scholar with Doctor–Patient Communication, Patient Satisfaction, and Consultation Length as the keywords, restricting the academic journals and articles published between 2002 and 2016. Research showed that the average consultation length of doctor–patient communication appears to be positively related to the patient satisfaction. The length of consultation time was on average 6.9–12.4 minutes. Increasing effective communication is generally associated with increased patient satisfaction with consultation time. It is essential that doctors spend time with patients to communicate adequately in relation to their illness. Keywords: doctor–patient communication, patient satisfaction, consultation length